FAKTOR – FAKTOR YANG MEMPENGARUHI KECERDASAN INTELEKTUAL (IQ) DAN KECERDASAN EMOSIONAL (EQ) MAHASISWA JURUSAN GIZI POLTEKKES KEMENKES RIAU - Shally Febrindah; Muharni Harahap; Fitria Gusfa (JURNAL PROTEKSI KESEHATAN, 2014)
Factors That influence Intelectual Question Student of Departement of Nutrition of Riau Health Politechnique. The adequate nutrition and fulfill the body need is the main determinant in brain growth and development. Brain growth and development determine the intelligence of human being. Purpose of the research to understand factors that influence IQ and EQ Student of Departement Nutrition of Riau Health Politechnique. The research as about analytic descriptive which cross sectional study design. The result of this research is respondent which low nutrient status have low IQ which 21,7%. Respondent which high care pattern have average IQ which 56,7%. Respondent which high social economic have average IQ which 58,3%. Respondent which normal and low nutrient status have high EQ which each 41,7%. Respondent which high care pattern have high EQ which 78,3%. Respondent which high social economic have high EQ which 80%.